POSISI DAN FUNGSI TEORI DALAM PENELITIAN KUALITATIF - Madekhan Madekhan (Universitas Islam Lamongan, 2018)
There is a growing interest on qualitative methodology as evidence by an increasing number of qualitative research design employed in social science researches. In qualitative inquiry process, the role of theory in the field of social science and where it situates in the research framework has always created a challenge for the researchers. However, inconclusive and differing opinions have so far been documented about the position and function of theory in qualitative research. The purpose of this paper is to build a general perspective in terms of the position and function of theory in qualitative research methodology applicable to social science research. Review of literatures on these issues were presented and discussed. As a result, mostly argue that theory in qualitative research is not in terms of testifying the validity or accuracy, event or experience in real-life cannot always or necessarily be based on theory, yet the significant role of theory in literature review is an undeniable fact. Here, theory is road guidance in qualitative research. Key Words: Qualitative, Social Research, Position and Function of Theory